(untitled) (Ustozlar uchun, 2025)
This article discusses the main goals and objectives of teachers in the classroom. It emphasizes the importance of creating a positive and inclusive learning environment, promoting critical thinking, motivation, and continuous professional development. The article highlights how teachers play a vital role in shaping students’ intellectual and emotional growth through effective teaching and assessment strategies.